متطلبات تطبيق المحاسبة البيئية في المؤسسات الصناعية الجزائرية - سعيداني، محمد السعيد Saidani, Mohammed Alsaid (جامعة حسيبة بن بو علي بالشلف - مخبر العولمة واقتصاديات شمال إفريقيا, 2019)
This study aims to explore the Environmental Accounting application requirements in Algerian industrial institutions, and shed the light on difficulties which these types of institutions could face, we took a sample of accounting sections employees from 42 diffrent companiese. 78 questionnaires were answered out of 92 distributed. The results were as the following: - the awareness absence of environmental accounting concept in the Algerian industrial institutions. - The absence of the Environmental Accounting application requirements in the Algerian industrial institutions.
Keywords: البيئة -- المحاسبة البيئية -- المؤسسات الصناعية -- الجزائر